PELEPASAN SULFUR PADA TANAH SAWAH - Linca Anggria; Antonius Kasno; Tia Rostaman (Agric, 2019)
The objective of this study was to determine the release of S in paddy soil. The experiment was carried out in the greenhouse which the soil sample was taken from three different sites. The treatment consists of (T0) control, (T1) 0.02 g S pot-1, (T2) 0.04 g S pot-1, (T3) 0.08 g S pot-1, (T4) 0.04 g S pot-1 + rice straw. The concentration of S was measured in soil, surface water (soil solution) and leached water. The results showed that the addition of S increased the available S. In general, concentration of S in soil was high for site 1 and 3. It was possible due to the higher clay content for site 1 and 3 compared to site 2. The higher S concentration in soil solution was obtained by treatment T3 for all sites. Sulfur concentration in leached water was higher for T2 compared to T4. It indicated that rice straw could protect the release of S in leached water.